2021
DOI: 10.1155/2021/6645203
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rates of Microbial Communities from Livestock Waste to Soils: A Comparison between Compost and Digestate

Abstract: Livestock waste-based products, such as composted manure, are often used in crop production systems. The products’ microbial characteristics differ depending on animal waste treatment methods used (e.g., biogas production/composting). The question remains whether different livestock waste-based products differently impact soil microbiota. A pot experiment with five treatments (control, chemical fertilizer, digestate + chemical fertilizer, wheat straw compost + chemical fertilizer, and woodchip compost + chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…It is not surprising that the majority of the compost microbes were detected 3 months after incorporation into the soil since compost and soil share similar aerobic conditions as well as the majority of the microbes (Mehta et al, 2014). However, this contradicts other research, which found that compost had more extensive effects on soil microbial structure than digestate, and that digestate mainly affected the abiotic properties of soil (Akari and Uchida, 2021). Ferment and digestate are notably different from soil in terms of their physicochemical properties, leading to fewer ferment and digestate microbes being detected in the soil compared with compost and the selection of native soil microbes after incorporation (Andreev et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…It is not surprising that the majority of the compost microbes were detected 3 months after incorporation into the soil since compost and soil share similar aerobic conditions as well as the majority of the microbes (Mehta et al, 2014). However, this contradicts other research, which found that compost had more extensive effects on soil microbial structure than digestate, and that digestate mainly affected the abiotic properties of soil (Akari and Uchida, 2021). Ferment and digestate are notably different from soil in terms of their physicochemical properties, leading to fewer ferment and digestate microbes being detected in the soil compared with compost and the selection of native soil microbes after incorporation (Andreev et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…More information is needed on the microbial community composition and diversity of untreated and lagoon-stabilized DE and its seasonal variability. Other studies have proposed that the impact and the survival rate of microbes from manure waste-based products on soil microbiomes largely depend on the type of treatment applied to manure [ 12 ]. Many studies focus on environmental risk assessment by studying antibiotic-resistant bacteria or their genes.…”
Section: Introductionmentioning
confidence: 99%